Well, first thing we need to do is put this in slope intercept form of y.
Subtract 9 from both sides to isolate "y".
y= -3x-9
Now we can graph the equation
Graph the point (0,-9) since it is the y-intercept.
To get the x intercept, isolate the "x" variable instead of "y".
y+9 = -3x
(Divide every number on both sides of the equation by -3 to isolate "x".)
y/-3 -3= x
now that this is in slope intercept form of x, plug in 0 for y to get the number for x when y is 0.
0/-3 -3 = x
-3 = x.
Graph (-3, 0). Connect this point to the point (0,-9) and you get have successfully graphed the equation y+9= -3x.
I hope this helped.